Fe/HZSM-5 catalyzed liquefaction of cellulose assisted by glycerol - Jingjing Li; Guangfu Qin; Xiaodong Tang; Chengxin Xiang (Catalysis Communications, 2021)
Fe/HZSM-5 catalyst was prepared by the impregnation method and employed for the liquefaction of cellulose at 350 °C for 30 min. Iron changed the surface acidity of HZSM-5 and provided stronger acid sites. Fe/HZSM-5 improved the yield of bio-oil, and the coke formation was inhibited compared to HZSM-5 alone. The presence of glycerol and Fe/HZSM-5 promoted both the hydrodeoxygenation (HDO) and aromatization reactions. Ketones yields decreased from 29% to 7%, and the content of aromatics and furans increased significantly. The possible hydrogen supply mechanism of glycerol and the route of cellulose liquefaction were proposed.